Application of MMS Data to Road Bridge Maintenance Management - T. Misaki; K. Ogawa; S. Nishiyama; M. Yamamoto; K. Kimoto (The International Archives of the Photogrammetry, Remote Sensing and Spatial Information Sciences, 2025)
In Japan, as many road structures age and labor shortages arising from a declining birthrate and aging population coincide with increasingly severe disasters, there is a growing need for efficient maintenance management. I-Construction 2.0 is progressing, and ICT construction and the 3D modeling of construction work using BIM/CIM which is Linking surveying design construction maintenance management with 3D data are underway. In addition, for the purpose of efficient road management, 3D data of expressways and national highways nationwide are being acquired and stored in MMS. Mobile Mapping System is a system that acquires 3D spatial information on the road and its surroundings while driving. However, despite this background, effective utilization of 3D data in maintenance management has not been well demonstrated. This study aimed to utilize 3D data for maintenance management by extracting deformations from two-period 3D datasets. Specifically, the deformations were quantified by difference analysis using the M3C2 algorithm. The utilization of 3D data in maintenance management is also discussed.